2004
DOI: 10.1162/0898929041920496
|View full text |Cite
|
Sign up to set email alerts
|

Development of Brain Mechanisms for Processing Orthographic and Phonologic Representations

Abstract: Developmental differences in the neurocognitive networks for lexical processing were examined in 15 adults and 15 children (9- to 12-year-olds) using functional magnetic resonance imaging (fMRI). The lexical tasks involved spelling and rhyming judgments in either the visual or auditory modality. These lexical tasks were compared with nonlinguistic control tasks involving judgments of line patterns or tone sequences. The first main finding was that adults showed greater activation than children during the cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
189
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(216 citation statements)
references
References 88 publications
22
189
5
Order By: Relevance
“…Even though we cannot fully exclude the possibility of syllabic representation to drive IPG, we suggest -in line with Binder et al (1999Binder et al ( , 2003 -that the critical difference between words and PWs is the semantic representation exclusive to words, a difference which dominates the differential IPG activation for lexicality. This conclusion receives support from lesion studies of the IPG (see Price, 2000 for an overview), and is in line with the concept proposed by BOLD-contrast findings in studies on dyslexia (Booth et al, 2004;Horwitz et al, 1998;Pugh et al, 2000).…”
Section: The Lexicality Effectsupporting
confidence: 82%
See 1 more Smart Citation
“…Even though we cannot fully exclude the possibility of syllabic representation to drive IPG, we suggest -in line with Binder et al (1999Binder et al ( , 2003 -that the critical difference between words and PWs is the semantic representation exclusive to words, a difference which dominates the differential IPG activation for lexicality. This conclusion receives support from lesion studies of the IPG (see Price, 2000 for an overview), and is in line with the concept proposed by BOLD-contrast findings in studies on dyslexia (Booth et al, 2004;Horwitz et al, 1998;Pugh et al, 2000).…”
Section: The Lexicality Effectsupporting
confidence: 82%
“…Pugh et al (2000) provided evidence that dyslexia can be conceived as a disorder of relating print to sound and vice versa, which corresponds to a disruption of the projections between the IPG, and occipital as well as temporal cortical areas (Booth et al, 2004;Horwitz et al, 1998; but see Kronbichler et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, phonological representations may also be directly impacted by learning to read in a manner independent of these newly acquired links to orthography. It remains an empirical question as to which explanation is most likely but emerging fMRI evidence from adults and older children offers support for age-related increases in the recruitment of orthographic processing in rhyming tasks even when, as in the present study, these tasks are delivered exclusively in the auditory modality (Booth et al, 2004). Among adults, Pattamadilok et al (2011) found two ERP components associated with orthographic activation in auditory rhyme judgement: the first occurred during phonological segmentation, and the second, during the task decision process.…”
Section: Overviewmentioning
confidence: 51%
“…Previous research conducted by Booth and colleagues (Booth, et al 2003b;Booth, et al 2004;Booth, et al 2001) employed an auditory rhyme decision task, among other tasks, to compare language processing in adults versus children. One of these studies showed that both adults and children activated left inferior frontal gyrus, bilateral superior/middle temporal gyri, and left fusiform gyrus (Booth, et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…One of these studies showed that both adults and children activated left inferior frontal gyrus, bilateral superior/middle temporal gyri, and left fusiform gyrus (Booth, et al 2004). This study also reported that adults showed greater activation than children in left inferior frontal gyrus and left superior temporal gyrus, suggesting that adults engage these nodes of the language network to a greater degree than do children for phonological processing involved in rhyme decisions.…”
Section: Introductionmentioning
confidence: 99%